Dissecting microbial community structure and metabolic activities at an oceanic deep chlorophyll maximum layer by size-fractionated metaproteomics. (October 2020) - Xie, Zhang-Xian; He, Yan-Bin; Wang, Ming-Hua; Zhang, Shu-Feng; Kong, Ling-Fen; Lin, Lin; Liu, Si-Qi; Wang, Da-Zhi
Highlights: A holistic proteomic view of microbial community and metabolic activity at the DCM. Photoautotrophs, SAR11, NOB and archaea were key biogeochemical players. Carbon fixation and light utilization by non-photoautotrophs were vital at the DCM. Phytoplankton used DOM as alternative nutrients to support productivity of the DCM. Non-cellular bio-entities might play important roles in biogeochemical processes. Abstract: The deep chlorophyll maximum (DCM), a critical layer in the ocean characterized by the highest biomass and productivity, determines marine productivity, biogeochemical cycling and carbon sequestration. However, a comprehensive understanding of microbial community structure and metabolic activities in this layer is lacking in several parts of the oceans. Here, we characterized the whole spectrum of proteins covering three size fractions (0.7-200 µm, 0.2-0.7 µm, 10 kDa-0.2 µm) in the DCM of the South China Sea using a metaproteomic approach. A total of 17 724 non-redundant proteins were confidently identified. Proteins from Cyanobacteria, SAR11, nitrite-oxidizing bacteria, Archaea, eukaryotic phytoplankton and phototroph-associated viruses were abundant. These organisms were actively involved in diverse biogeochemical processes including light-dependent energy transduction, carbon fixation, nitrification, sulfur metabolism, dissolved organic matter (DOM) uptake, and C1 and methylated compounds oxidation. Furthermore, chemolithoautotrophic activity of Nitrospinae and Thaumarchaea complemented carbon fixation pathways in this habitat. Notably, photoheterotrophic activity of SAR11 and PVC (Planctomycetes, Verrucomicrobia and Chlamydiae) bacteria and mixotrophic activity of photoautotrophs suggested diverse regulation channels of light on microbe-mediated DOM recycling. This in-depth metaproteomic study provides a holistic view of microbial community and metabolic activities in the DCM, and uncovers novel biogeochemical processes, especially those previously ignored but potentially active in the smallest fraction.